Sa skya Paṇḍita on the defining characteristic and variegation of direct perception (based on his Tshad ma rigs gter with his auto-commentary and Go-rams pa’s sub-commentary providing contextual and subtextual clarification) - Stewart, Bruce J. (Acta Orientalia Vilnensia, 2010)
Independent scholarThe present study focuses on the defining characteristic and variegation of direct perception (mngon sum, pratyakṣa) as laid out by Sa-skya Paṇḍita Kun-dga’ rgyal-mtshan (1182–1251) in the first eight verses of the ‘Direct Perception’ chapter in his Tshad-ma rigs pa’i gter. As is well known, direct perception along with inference (rjes dpag, anumāna) make up the two means of valid cognition (tshad ma, pramāṇa) according the Buddhist system of epistemology initiated by the renowned Buddhist philosopher Dignāga (circa 480–540) and expanded and further developed by his indirect follower Dharmakīrti (mid-7th century). Each of these means of valid cognitionis restricted to its respective objects (prameya, gzhal bya); the specifically characterised object (rang mtshan, svalakṣaṇa) is the object of a direct perception and the generally characterised object (spyi mtshan, sāmānyalakṣaṇa) is the object for an inference.